A rare case of traumatic proximal corpus cavernosal fracture that presented only with perineal haematoma. (May 2022) - Kyriazis, Grigorios; Babu, Asrit; Smith, Nicholas; Youssef, Fady
We report a rare case of traumatic proximal corpus cavernosal tear following sexual intercourse that presented only with perineal haematoma and represents only the third reported similar case. The patient underwent a magnetic resonance imaging scan of the pelvis and penis due to the atypical presentation and was subsequently taken to theatre for exploration and repair of the injury. Although uncommon, clinicians should be aware of this clinical condition, as early recognition with early surgical treatment can potentially decrease the incidence of late complications of fibrosis, angulation and impotence.